Orwell : Life and Art - Meyers, Jeffrey (Book collections on Project MUSE., 2010)
This remarkable volume collects, for the first time, essays representing more than four decades of scholarship by one of the world's leading authorities on George Orwell. In clear, energetic prose that exemplifies his indefatigable attention to Orwell's life work, Jeffrey Meyers analyzes the works and reception of one of the most widely read and admired twentieth-century authors.;; Orwell: Life and Art covers the novelist's painful childhood and presents accounts of his autobiographical writings from the beginning of his career through the Spanish Civil War. Meyers continues with analyses of Orwell's major works, including Animal Farm and Nineteen Eighty-Four, as well as his style, distinctive satiric humor, and approach to the art of writing. Meyers ends with a scrupulous examination of six biographies of Orwell, including his own, that embodies a consummate grasp and mastery of both the art of biography and Orwell's life and legacy.;; Writing with an authority born of decades of focused scholarship, visits to Orwell's homes and workplaces, and interviews with his survivors, Meyers sculpts a dynamic view of Orwell's enduring influence on literature, art, culture, and politics.